Stylistyczna funkcja barw w powieści Kollokacja Józefa Korzeniowskiego - Żurawska-Chaszczewska, Jowita (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2012)
Korzeniowski’s novel features different colours (white, yellow, red, green, skyblue (azure), brown, pink, orange, gray and black) that describe and specify the appearance of the protagonists, their places of abode and the surrounding nature. The significance of these ”primary” colours are then complemented with a special vocabulary of light and shade that renders not only the beauty of the characters in the novel but chiefly their emotions and experience. The colours are to distinguish and differentiate the protagonists of the book, who are identifiable by coded references to colours. They are representatives of the local petty gentry, impecunious minor noblemen, who nevertheless live sumptuously and above their station and the colours are to show their bad taste and poor choices. This group is contrasted by a traditionally living family of the Starzyckis, who are faithful to their tradition and live a modest and orderly life, while their ideals concerning order and modesty can be seen even in their dress. Thus, the colours attributed to them and to their environment are to reevaluate virtues, highlight values and those traits of character that the author of the novel considered most important. Fanciful and colourful little things as well as the colours used in the descriptions of nature underline the realism of the setting in the novel. Colours in Kollokacja are mainly evoked in the linguistic creation of the protagonists and their emotions, whereas much more sparingly in descriptions of manors, houses and nature, which emphasizes even more the dominant role of the characters of the novel and the subordinate role of nature and the description of villages and cottages as the setting for the novel.